In order to find the answer you will have too divide 58 by 18 and then divide what you get from that by 100 to get your answer.
100%/x%=58/18
(100/x)*x=(58/18)*x
100=3.22222222222*x
(3.22222222222) to get x
100/3.22222222222=x
x=31.0344827586
Therefore your answer is "31%."
Hope this helps.
Given function is
![f(x)=\left\{\begin{matrix}3x+k & x\leq -4 \\ kx^2-5 & x> -4\end{matrix}\right.](https://tex.z-dn.net/?f=f%28x%29%3D%5Cleft%5C%7B%5Cbegin%7Bmatrix%7D3x%2Bk%20%26%20x%5Cleq%20-4%20%5C%5C%20kx%5E2-5%20%26%20x%3E%20-4%5Cend%7Bmatrix%7D%5Cright.)
now we need to find the value of k such that function f(x) continuous everywhere.
We know that any function f(x) is continuous at point x=a if left hand limit and right hand limits at the point x=a are equal.
So we just need to find both left and right hand limits then set equal to each other to find the value of k
To find the left hand limit (LHD) we plug x=-4 into 3x+k
so LHD= 3(-4)+k
To find the Right hand limit (RHD) we plug x=-4 into
![kx^2-5](https://tex.z-dn.net/?f=kx%5E2-5)
so RHD= ![k(-4)^2-5](https://tex.z-dn.net/?f=k%28-4%29%5E2-5)
Now set both equal
![k(-4)^2-5=3(-4)+k](https://tex.z-dn.net/?f=k%28-4%29%5E2-5%3D3%28-4%29%2Bk)
![16k-5=-12+k](https://tex.z-dn.net/?f=16k-5%3D-12%2Bk)
![16k-k=-12+5](https://tex.z-dn.net/?f=16k-k%3D-12%2B5)
![15k=-7](https://tex.z-dn.net/?f=15k%3D-7)
![k=-\frac{7}{15}](https://tex.z-dn.net/?f=k%3D-%5Cfrac%7B7%7D%7B15%7D)
k=-0.47
<u>Hence final answer is -0.47.</u>
This is what i did to get the answer.
225/ 4.5 = 50 seconds to finish the slushy.
Answer:f(x)= -8 (4x) will be the reflected function across x-axis for the function g(x).
Explanation: since we know that the image or reflection of x along x-axis = -x
That is, when we talk about a function's reflection across any axis then we have to replace variable according to that axis. For example if you have a line x=3 in positive x-axis then you can also draw a similar line x=-3 in negative x-axis. so, you can say, x=-3 is the reflection of x=3 along x axis.
Similarly, for an another line y=3, y=-3 is a reflection.
thus in the case of g(x) we can find the reflection across x-axis after replacing x by -x.
we have g(x) =8(4x)
replace x by -x we get g(-x)= 8(4×-x)= 8(-4x)=-8(4x)
so -8(4x) is the reflection of g(x)
but according to the question f(x) is the reflection of g(x) across x-axis.
Thus, f(x)=-8(4x)